MENINGKATKAN PENGETAHUAN MENINGKATKAN PENGETAHUAN SAINS MELALUI METODE KARYAWISATA PADA ANAK USIA 4-5 TAHUN TK BINTANG KECIL KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Norma Yannaila; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Knowledge of science children aged 4-5 years Little Star Nursery District of Bangko Rokan Hilir, is still low due to a child less able to plan an idea or ideas to know the things that is around children, not knowing the objects that exist in the school environment , lack of instructional media used in the learning process of teachers in the classroom. The purpose of this research is to improve scientific knowledge of children aged 4-5 years Little Star Nursery through metude field. This research is a classroom action research, research data obtained through observation and documentation. This research was conducted through two cycles. In the second cycle to increase children's knowledge of science was 69.4%. It can be concluded that by applying the method of field can improve scientific knowledge of children aged 4-5 years in kindergarten Little Star District of Bangko Rokan Hilir.Keywords: Kids Science Knowledge, Methods Leisure